2019
DOI: 10.13075/mp.5893.00773
|View full text |Cite
|
Sign up to set email alerts
|

The association between the Mediterranean diet and high physical activity among the working population in Croatia

Abstract: Background: Unhealthy eating habits and physical inactivity constitute an emerging public health problem. The working population is of special interest for public health monitoring and evaluation because workers' unhealthy lifestyles may lead to reduced work ability. The aim of this study was to determine diet quality and adherence to the Mediterranean diet (MD), according to the level of physical activity, and to detect variables associated with the working population's being highly physically active. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
2
9
0
2
Order By: Relevance
“…In Western countries, and to a lesser extent in Mediterranean countries, people with a preference for wine have, in general, healthier dietary habits than individuals with other preferences. Consistent with previous studies [ 76 , 86 ], work-related physical activity and leisure-time physical activity were found to be related to better diet quality. Eating behavior and physical activity both use the same decision-making process, which involves self-regulation mediated by the neural system [ 87 ].…”
Section: Discussionsupporting
confidence: 91%
“…In Western countries, and to a lesser extent in Mediterranean countries, people with a preference for wine have, in general, healthier dietary habits than individuals with other preferences. Consistent with previous studies [ 76 , 86 ], work-related physical activity and leisure-time physical activity were found to be related to better diet quality. Eating behavior and physical activity both use the same decision-making process, which involves self-regulation mediated by the neural system [ 87 ].…”
Section: Discussionsupporting
confidence: 91%
“…The covariates were selected according to the previous literature. Physical activity [24], socioeconomic position based on income [25], education [26], alcohol consumption [27], and nutritional status [28] are the direct influencing factors for diet quality. All models were adjusted for these covariates in multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, some studies showed that regular physical activity were associated with healthier eating habits (Pavičić ŽeŽelj et al, 2019). Further, physical activity and healthful eating habits were also associated with improvements in immune system function (Defagó et al, 2019;Weyh et al, 2020), which in turn, may reduce one's risk for developing COVID-19 symptoms or complications (Hamer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%